Development of a new model of reconstituted mouse epidermis and characterization of its response to proinflammatory cytokines. (26th June 2017) - Pohin, Mathilde; Veaute, Carolina; Garnier, Julien; Barrault, Christine; Cronier, Laurent; Huguier, Vincent; Favot, Laure; Mcheik, Jiad; Bernard, François‐Xavier; Lecron, Jean‐Claude; Morel, Franck; Jégou, Jean‐François
Abstract: The development of three‐dimensional models of reconstituted mouse epidermis (RME) has been hampered by the difficulty to maintain murine primary keratinocyte cultures and to achieve a complete epidermal stratification. In this study, a new protocol is proposed for the rapid and convenient generation of RME, which reproduces accurately the architecture of a normal mouse epidermis. During RME morphogenesis, the expression of differentiation markers such as keratins, loricrin, filaggrin, E‐cadherin and connexins was followed, showing that RME structure at day 5 was similar to those of a normal mouse epidermis, with the acquisition of the natural barrier function. It was also demonstrated that RME responded to skin‐relevant proinflammatory cytokines by increasing the expression of antimicrobial peptides and chemokines, and inhibiting epidermal differentiation markers, as in the human system. This new model of RME is therefore suitable to investigate mouse epidermis physiology further and opens new perspectives to generate reconstituted epidermis from transgenic mice.